Factors influencing low female representation in pilot training recruitment. (January 2022) - Marintseva, Kristina; Mahanecs, Artjoms; Pandey, Mukesh; Wilson, Neil
Abstract: In 2011 ICAO published a report about projected pilot and training capacity shortage (ICAO, 2011). To solve this problem, several studies have been carried out, and forecasts of the required number of pilots for the next 10–20 years are constantly being updated. Universities have begun introducing pilot training into their aviation courses, although only US airlines require a degree from the candidates to work as a pilot. The leading providers of pilot training facilities and industry observers argue that even with severe flight restrictions due to COVID-19, the shortage of pilots and quality pilot training remains a major concern. There is a trend of under-representation of females in the pilot roles. Some researchers and aviation industry experts assume that more women should be recruited into the profession to address the pilot shortage. This paper explores the current key reasons for the low female representation in pilot training recruitment. In many studies, the problem of gender discrimination and societal stereotype that believes that the pilot is a purely male type of job are dominant among the negative ones. The authors investigated whether these factors are seen as predominant in women's career decisions in aviation. A qualitative study was conducted utilising the semi-structured in-depth interview of nine female pilots from Europe, Australia and UK. A transcript based content analysis was done using Nvivo. Further, the triangulation method was utilized to verify the results of the study. The main findings from this research show that, in addition to the high cost of training and the tendency of airlines to shift financial obligations for training to students, the hiring of pilots continues to suffer from gender inequality. Reasons such as "Lack of role models for young girls and women in aviation", "Cultural sexism" and "Lack of acceptance from male peers and passengers" continue to hinder the promotion of the pilot profession among women. Multiple organisations and airlines have initiatives in place to mitigate the problems connected with pilot training and hiring. However, the effectiveness of these initiatives is controversial, as the number of female pilots has seen hardly any growth in the past ten years. Furthermore, they may be responsible in future for creating an even more "gender-unequal" culture inside the industry, as women will be seen in their roles only due to gender recruitment requirement. All stakeholders, including universities that choose to participate in the pilot training process, could help rethink the principles of gender balance, increasing the visibility of their initiatives and raising public awareness of the availability of pilot training and career prospects for women. The article presents the theoretical and practical implications of the reasons for low female representation in pilot training recruitment. Highlights: Despite numerous initiatives to attract females to pilot careers, there has been a negligible increase in their number. Role models, mentors, a personal life and support are key factors that women will look to when they plan to become pilots. Career planning support is key given the high cost of training, health risks and instability in the industry.